The Figurative Languages Found in the Novel: Romance of the Three Kingdoms by Luo Guanzhong - priyoto, priyoto; Zidane, Zidane (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
This study aims to analyze the types of figurative language used in the novel “Romance of the Three Kingdoms” by Luo Guanzhong. The research adopts a qualitative method, relying on factual data from the literary work itself and expert quotations. The focus theory is figurative language, which one of the branches in Semantics approach. The findings reveal that out of the 13 types of figurative language, only four were identified in the novel. Hyperbole accounted for 33.79% of the sentences, personification for 26.21%, symbolism for 11.03%, and metaphor for 28.97%. In the end, the writer concludes that there are only four types of figurative language out of thirteen, revealing hyperbole, personification, symbolism, and metaphor. The findings showcased the author's skillful use of language, it can be seen through the analysis in a findings and discussion session. With hyperbole emphasizing characters' emotions, personification highlighting destiny and unity, symbolism conveying deeper meanings, and metaphor foreshadowing future events. These analysis underscored the richness of figurative language in enhancing storytelling. The study invites readers to delve into the world of figurative language, appreciating its impact on narrative depth and reader engagement